1979
DOI: 10.1037/0022-0167.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the two-chair experiment and empathic reflections at a conflict marker.

Abstract: The differential effects of a Gestalt counseling operation and empathic reflections of feeling on client depth of experiencing, change in awareness, and goal attainment were studied in a counseling analogue. Using four counselors and 16 subjects as their own controls, each of the operations was applied to each subject to facilitate resolution of personally meaningful conflicts. Results showed that depth of experiencing and change in awareness were significantly higher for the subjects following the Gestalt ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 14 publications
0
29
0
2
Order By: Relevance
“…A method shown to be effective in the reconciliation of opposites in the personality is the Gestalt two-chair operation (Greenberg, 1979;Greenberg & Clarke, 1979;Greenberg & Dompierre, 1981;Greenberg & Rice, 1981). This procedure facilitates a dialogue between the two sides in order to bring the opposing parts into contact.…”
mentioning
confidence: 99%
“…A method shown to be effective in the reconciliation of opposites in the personality is the Gestalt two-chair operation (Greenberg, 1979;Greenberg & Clarke, 1979;Greenberg & Dompierre, 1981;Greenberg & Rice, 1981). This procedure facilitates a dialogue between the two sides in order to bring the opposing parts into contact.…”
mentioning
confidence: 99%
“…Bohart (1977) found that an empty chair dialogue with an imagined provocateur was more effective than was emotional discharge, intellectual analysis, or no treatment for relieving anger and hostile attitudes. In other studies, a Gestalt two-chair technique resulted in greater depth of experiencing and greater shifts in awareness than did counselors' empathic reflection (Greenberg & Clarke, 1979;Greenberg & Dompierre, 1981). The two-chair technique allowed clients to experience and confront internal conflicts in the present, which led to a greater sense of internal conflict resolution.…”
Section: Goal 2: Expression Of Angermentioning
confidence: 90%
“…To date, empirical research in this area has been sparse and disconnected. In a series of experiments during the past decade, Greenberg and his colleagues have compared the effects of the Gestalt two-chair exercise with the effects of empathic reflection (Greenberg & Clarke, 1979;Greenberg & Dompierre, 1981), emotional focusing (Greenberg & Higgins, 1980), and rational problem solving (Clarke & Greenberg, 1986) on the resolution of decisional conflicts. In general, they found the twochair exercise to be most effective in increasing decisionmakers' awareness of and resolution to their conflicts.…”
Section: Evaluation Of the Interventionsmentioning
confidence: 99%